2021
DOI: 10.5606/tftrd.2021.5433
|View full text |Cite
|
Sign up to set email alerts
|

Pregabalin as a probable cause of central serous chorioretinopathy: Two case reports

Abstract: Pregabalin is commonly used for the treatment of neuropathic pain and is attributed to adverse effects of peripheral vasodilation and peripheral edema. Central serous chorioretinopathy (CSCR) is characterized by choroidal fluid leaks from choroidal vessels under the retina, causing focal retinal detachment with macular vision loss. Herein, we report two cases admitted to our clinic with vision loss while under pregabalin treatment. Upon eye examination, both patients were diagnosed with acute CSCR. Pregabalin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Pregabalin as an L‐type calcium channel antagonist can lead to vasodilation of choroidal vessels in BRB which can cause retinal oedema (Makani et al, 2011). Most recently, it was associated with the development of central serous chorioretinopathy (Doğan et al, 2021). Herein, we found that it could also be associated with an increased risk of DME in persons with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Pregabalin as an L‐type calcium channel antagonist can lead to vasodilation of choroidal vessels in BRB which can cause retinal oedema (Makani et al, 2011). Most recently, it was associated with the development of central serous chorioretinopathy (Doğan et al, 2021). Herein, we found that it could also be associated with an increased risk of DME in persons with diabetes.…”
Section: Discussionmentioning
confidence: 99%